Prominently Increased of Mannose Binding Lectin (MBL) and Myeloperoxidase (MPO) Levels in Severe Valve Regurgitation and Heart Failure of Rheumatic Heart Disease - Putri, Rachmania; Suwarniaty, Renny; Fitri, Loeki Enggar; Nugroho, Susanto; Rahman, Mohammad Saifur (Journal of Tropical Life Science, 2017)
Rheumatic heart disease (RHD) is mediated by an abnormal immunological response following a Streptococcus pyogenes infection that induces a disturbance of oxidants and antioxidants balances. Mannose-binding lectin (MBL) binds to N-acetylglucosamine, a molecule present on the Streptococcus cell wall and human heart valves. There is a disturbance of oxidant and antioxidant balance in rheumatic disease. Myeloperoxidase (MPO) is a marker of oxidative stress and inflammation. This study was aimed to determine the correlation of MBL and MPO levels and severity of valvular regurgitation and heart failure (HF) in RHD patients. A case-control study was conduct using human peripheral blood samples from 32 children aged 6 to 14 years old. The subjects were divided into two groups: 16 RHD patients included in the case group and 16 healthy children as a control group. The level of MBL and MPO was investigated using ELISA method. There were significant differences on MBL and MPO level between patient and control group. The level of MBL and MPO were significantly increased in RHD group, especially on severe valvular regurgitation. There was a strong correlation between MBL and MPO levels and the severity of valvular regurgitation (r = 0.94 and r = 0.88). The least significant diff-erence (LSD) analysis showed that significant difference occurs in the severe heart failure group. Our research revealed that the MBL and MPO levels in pediatric RHD patients were significantly higher than in healthy children. The MBL and MPO levels were significantly correlated with the severity of valvular regurgitation and heart failure.